2022
DOI: 10.1155/2022/1869922
|View full text |Cite|
|
Sign up to set email alerts
|

Gait Improvement in Patients with Knee Osteoarthritis after Proximal Fibular Osteotomy

Abstract: Proximal fibula osteotomy (PFO) is a relatively new surgery to treat medial compartment knee osteoarthritis (KOA), which can improve varum deformity and relieve knee joint pain. However, the gait alterations in KOA patients after PFO are still poorly understood. The purpose of this study was to evaluate the gait patterns change in patients of medial compartment KOA after PFO. Gait data were collected for 9 females with unilateral medial compartment KOA before and at 6 months after PFO and also for 9 healthy ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Clinically, for patients with many complications and poor surgical tolerance, PFO can be preferred. In view of the heterogeneity and different follow-up time, whether these conclusions are applicable should be further determined in future studies [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, for patients with many complications and poor surgical tolerance, PFO can be preferred. In view of the heterogeneity and different follow-up time, whether these conclusions are applicable should be further determined in future studies [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%